In Silico and In Vitro Study of Rice Bran Peptides for the Treatment of Oxidative Stress Diabetes and Hypertension - Amin, Md. Ruhul; Mojumder, Md Nijamuddin; Rahman, Md Ratul; Ferdous, Nilufa; Faruque, Md. Omar; Siddiquee, Muhammad Ali; Howlader, Zakir Hossain; Alauddin, Md (Cardiology and Cardiovascular Medicine, 2024)
The study explores the health benefits of rice bran protein hydrolysates and bioactive peptides, focusing on their anti-oxidative, anti-diabetic, and anti-hypertensive properties through in-silico and in-vitro analyses. Rice bran proteins were isolated and in vitro enzymatically digested to assess soluble peptide concentration, degree of hydrolysis (DH), anti-oxidative properties, and inhibitory activity against α-amylase and angiotensin- I-converting enzyme (ACE). This study indicates a higher degree of protein hydrolysis (84.0-99.1%) in various rice bran protein fractions, demonstrating increased hydrolysis with both single and multiple enzyme digestion. The alcalase enzyme was notably efficient for the DH of all protein hydrolysates, and the combination of enzymes (alcalase-trypsin) exhibited the highest DH in the prolamin fraction. Moreover, alcalasetrypsin (4h digested) demonstrated significant inhibitory activity against α-amylase and ACE, respectively. Additionally, in-silico studies were implemented to investigate bioactive peptides binding affinity to the target protein compared to reference drugs. Our study discovered that YY and IP peptides exhibit the highest binding affinity to ACE and α-amylase target proteins, respectively. Moreover, these peptides demonstrated favorable oral bioavailability and non-toxic behavior compared to reference drugs in molecular dynamics (MD) simulations. This encourages the development of nutraceuticals and dietary supplements based on rice bran protein hydrolysates, supported by additional in-vivo research.